2010
DOI: 10.1111/j.1365-2567.2010.03270.x
|View full text |Cite
|
Sign up to set email alerts
|

A critical function of toll‐like receptor‐3 in the induction of anti‐human immunodeficiency virus activities in macrophages

Abstract: SummaryToll-like receptor-3 (TLR-3) recognizes double-stranded RNA and induces multiple intracellular events responsible for innate anti-viral immunity against a number of viral infections. Activation of TLR-3 inhibits human immunodeficiency virus (HIV) replication, but the mechanism(s) underlying the action of TLR-3 activation on HIV are largely unknown. Here we demonstrate that treatment of monocyte-derived macrophages with poly I:C, a synthetic ligand for TLR-3, significantly inhibited HIV infection and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 46 publications
4
109
1
3
Order By: Relevance
“…However, we demonstrated that, although IFN-␣/␤ could induce the expression of anti-HIV RNAs (miRNA-28, miRNA-125b, miRNA-150, and miRNA-382) ( Figure 2C), they failed to induce anti-HIV miR-223 expression in monocytes (data not shown). This finding is in agreement with a previous publication 42 showing that IFN-␣/␤ had little effect on miRNA-223 expression in macrophages. Thus, it is likely that the adverse effect of morphine on anti-HIV miRNAs may be through its negative impact on endogenous IFN-␣/␤ expression in monocytes.…”
Section: Discussionsupporting
confidence: 94%
“…However, we demonstrated that, although IFN-␣/␤ could induce the expression of anti-HIV RNAs (miRNA-28, miRNA-125b, miRNA-150, and miRNA-382) ( Figure 2C), they failed to induce anti-HIV miR-223 expression in monocytes (data not shown). This finding is in agreement with a previous publication 42 showing that IFN-␣/␤ had little effect on miRNA-223 expression in macrophages. Thus, it is likely that the adverse effect of morphine on anti-HIV miRNAs may be through its negative impact on endogenous IFN-␣/␤ expression in monocytes.…”
Section: Discussionsupporting
confidence: 94%
“…98 Activation of TLR3 inhibits HIV replication in macrophages. 99 We observed that costimulation of PAR1 and TLR3 led to increased IFN-b-dependent responses in bone marrow-derived macrophages and dendritic cells. 46 It is therefore possible that PAR1 may also contribute to antiviral responses during HIV infection.…”
Section: Hivmentioning
confidence: 78%
“…After 16 hours, the culture medium was removed and fresh medium was added (to remove the ligands that may have direct anti-HIV activity in macrophages). 21 Culture supernatant (SN) was collected at 48 hours poststimulation for an IFN-b and IFN-l enzyme-linked immunosorbent assay (ELISA) and used to treat macrophages.…”
Section: Stimulation Of Ecs With Tlr and Rig-i Ligandsmentioning
confidence: 99%